Antenatal Care ( ANC ) Regularity Reviewed From Husband's Support and Pregnant Women's Attitudes at the Health Center Bankrupt Toli-Toli Regency in 2022 - Suriyanti; Anggrawati Wulandri (Journal of Health Science Community, 2024)
According to the 2017 SDKI data, the coverage of K4 pregnancy check-ups in Indonesia was 77%. Meanwhile, according to the 2018 Basic Health Research data, the proportion of K4 pregnancy check-ups in Indonesia was 74.1%, while the proportion of K4 pregnancy check-up history in Central Sulawesi province was 58.7%. Based on these data, it can be seen that the utilization of antenatal care services by a number of pregnant women in Indonesia is not fully in accordance with the established guidelines. The results of the initial data survey conducted by researchers at the Bangkir Health Center, Toli-Toli Regency in January 2022 obtained information from 10 pregnant women in TM III, 4 of whom routinely checked their pregnancies every trimester 1 to trimester 3 to health services. While the other 6 pregnant women said that they did not have regular pregnancy check-ups according to the schedule determined by health workers for various reasons, including no complaints, lack of husband support and negative attitudes of pregnant women towards ANC visits. Efforts that must be made are to provide counseling and socialization to pregnant women about the importance of regular antenatal care visits to improve maternal health. Design This research is a type of quantitative research with a design correlational . Respondents were taken with technique Accidental Sampling . With sample as many as 30 people. The Independent Variables are Husband's Support and Attitude. The dependent variable is the regularity of antenatal care visits. The results study Mostly known​ Respondent have support family  category not enough  that is totaling 17 people (56.7%). Most of them Respondent have attitude category attitude negative  that is totaling 16 people (53.3%) . Some of them big Respondent own regularity antenatal care visits in category No regular that is totaling 18 people (60%). Support Relationship husband with Regularity Antenatal Care Visits at the Health Center Bankrupt Toli-Toli Regency Year with a P-Value of 0.001 . H relationship between attitude with regularity Antenatal care visits at the health center Bankrupt Toli-Toli Regency in 2022. with a P-Value of 0.011 .